The Effect Of Environmental Performance On Profitability With Environmental Disclosure As Moderating - Ramlawati Ramlawati; Asriani Junaid; Syarifah Nurhalisa Alattas; Muslim Muslim (Jurnal Akuntansi, 2022)
Profitability describes a company's capacity to generate profits. Profitability is typically increased by implementing a nonexistent budget system, reducing marketing expenses, and implementing other asset management strategies. However, asset management is not the only factor affecting profitability in this instance. Environment, society, and economy have a fundamentally interdependent relationship. The company's existence in the environment has direct or indirect effects on the environment and social reality. Additionally, the company has great potential to alter the community's environment; therefore, the company's profitability improvement strategy must incorporate environmental considerations. This study focuses on 15 companies listed on the Indonesia Stock Exchange in 2018-2020 that received environmental performance ratings from PROPER. Quantitative research utilizing secondary data is conducted in the present study. Purposive sampling was used to carry out the sampling technique. Multiple moderation linear regression analysis, classical assumption testing, and hypothesis testing were employed in the investigation. The results indicated that environmental performance had a positive and statistically significant effect on profitability, with a significance level of 0.000. With a significant value of 0.000, the environmental disclosure variable strengthened the relationship between environmental performance and profitability.